Outcome of paraquat poisoning patients admitted in a tertiary hospital in Bangladesh - Khan, Faisal Bin Selim; Rahman, Abu Shahin Mohammed Mahbubur; Haque, Md Zahirul; Rahman, M Khalilur (TAJ: Journal of Teachers Association, 2023)
Background: Paraquat Poisoning is not unknown in clinical practice. However, the data from our country is scanty. Therefore, to find the outcome of paraquat poisoning in a tertiary level hospital was the objective of this study. Methods: The study was a longitudinal descriptive study and conducted at department of Medicine, Rajshahi Medical College Hospital. Patients of paraquat poisoning were approached for inclusion. Informed written consent was taken from the patients and/or attendants. Data were collected by face-to-face interview by the researcher with an aid of a semi-structured questionnaire. All available investigation reports, follow up notes, discharge papers and death certificates were scrutinized. A total 30 patients were included in this study. Results: Total 30 subjects were interviewed. Mean age was 25.33±8.86 (SD) years with female to male ratio-2:1.Majority were from rural area (90%). About 94% consumed with an intention of suicide. Most of the patients had renal impairment (53.3%) and hepatic impairment (50%) as complication. 63.3% patients reached to hospital >12 hours after ingestion of poison and 36.7% reached within 12 hours. Of all, 33.3% (n=10) patients survived. Possible cause of death were Multi organ failure (MOF) (40.0%), Acute renal failure (25.0%), ARDS (15.0%) and Hepatic failure (20.0%). However, overall outcome is not dependent with to time reaching hospital after poisoning but with amount of poison ingested (p<0.05). Conclusion: About 67% patients died following ingestion of the paraquat poisoning and it is not dependant with the time required to reach the hospital rather to the amount of poison ingested. TAJ 2023; 36: No-2: 35-46